Energirenoveringer af huse tjener sig ind over varmeregningen: Ikke via salgsprisen - Alessandro Tang-Andersen Martinello; Niels Framroze Møller (Danmarks Nationalbank, 2022)
The majority of energy renovations of houses cost more than they increase the sales price. This holds particularly in the metropolitan area and Aarhus, but also in a number of rural areas. Renovations that increase the sales price more than the renovation costs reduce CO2 emissions only marginally and are typically only possible for houses in and around the medium to large towns and more generally in the geographically more central parts of the country.
Keywords: 330; Gebäudesanierung; Energiesparendes Bauen; Immobilienpreis; Räumliche Verteilung; Raumheizung; Kosten; Dänemark